2013
DOI: 10.5559/di.22.4.02
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception Related To (Il)licit Substance Use and Attitudes Towards Its' Use and Legalization – the Role of Age, Gender and Substance Use

Abstract: The aim of this study was to determine the role of age, gender and tobacco, alcohol and marijuana use in relation to different aspects of attitudes toward (il)licit substance use. Differences in risk perception and attitudes toward substance use were assessed between groups of active substance users, ex-substance users, and non-substance users with regard to their age and gender. Respondents generally associated moderate risk with using tobacco/alcohol/marijuana and large risk with using ecstasy/cocaine/ heroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
1
10
0
6
Order By: Relevance
“…It is plausible to explain that gender differences in risk perception could be at least partially attributed to gender socialization (24), the fact that women have less power and control (25). In other words, males are typically assumed to frequently experiment various risk behaviours compared to females due to traditional social role and more conforming behaviour in our society (26), In addition, it is well known that adult women are more aware of health warnings associated with various health risks and use health services more than men (27). Given this level of interest and awareness in health, it may be reasonable to suggest that females have every reason to perceive unrealistically.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible to explain that gender differences in risk perception could be at least partially attributed to gender socialization (24), the fact that women have less power and control (25). In other words, males are typically assumed to frequently experiment various risk behaviours compared to females due to traditional social role and more conforming behaviour in our society (26), In addition, it is well known that adult women are more aware of health warnings associated with various health risks and use health services more than men (27). Given this level of interest and awareness in health, it may be reasonable to suggest that females have every reason to perceive unrealistically.…”
Section: Discussionmentioning
confidence: 99%
“…The perceived risk that is associated with the use of psychoactive substances is one such factor ( Johnston et al, 2015 ). Drugs that are perceived as more dangerous, such as heroin, are less commonly used than those that are perceived as less dangerous, such as marijuana ( Maričič, 2013 ; SEDRONAR, 2014 ). The perceived risk that is associated with marijuana use distinguished between college students who used marijuana from those who did not ( Kilmer et al, 2007 ; Lopez-Quintero et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Risk perception is modulated by sex ( Petronella-Croisant et al, 2013 ) and the frequency of drug use ( Thornton et al, 2013 ). Women perceived the use of alcohol, tobacco, and marijuana use as riskier compared with men ( Maričič, 2013 ; Petronella-Croisant et al, 2013 ), although both sexes had a similar level of risk perception for cocaine and heroin use ( Petronella-Croisant et al, 2013 ). Occasional consumption is perceived as less risky than regular consumption, which in turn is rated as less risky than daily use ( Thornton et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that women have more awareness and perception of health-related warning signs and use health services more frequently than men to maintain their health [ 82 , 83 ]. However, why the most ERP of female migrant construction workers do not significantly influence their physical or mental health in this paper?…”
Section: Discussionmentioning
confidence: 99%